1996
DOI: 10.4098/at.arch.96-24
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in thermogenesis and energy requirements of plateau pikas Ochotona curzoniae and root voles Microtus oeconomus

Abstract: . 1996. Seasonal variations in thermogenesis and energy requirements of plateau pikas Ochotona curzoniae and root voles Microtus oeconomus. Acta Theriologica 41: 225-236.The seasonal patterns of nonshivering thermogeneis (NST), resting metabolic rate (RMR) at 15°C and 25°C in plateau pikas Ochotona curzoniae (Hodgson, 1858) and root voles Microtus oeconomus (Pallas, 1776), from the Qinghai-Tibetan plateau, were determined and thermal conductance was calculated. NST tended to increase during cold season for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 23 publications
6
35
0
Order By: Relevance
“…Similar seasonal changes (i.e. SD-induced decreases in body mass and adiposity) have also been demonstrated in the European hamster (Cricetus cricetus; Canguilhem et al, 1988), montane vole (Microtus montanus; Petterborg, 1978), meadow vole (Microtus pennsylvanicus; Dark and Zucker, 1984), tundra vole (Microtus oeconomus; Wang and Wang, 1996) and bank vole (Clethrionomys glareolus; Peacock et al, 2004).…”
Section: Introductionsupporting
confidence: 64%
“…Similar seasonal changes (i.e. SD-induced decreases in body mass and adiposity) have also been demonstrated in the European hamster (Cricetus cricetus; Canguilhem et al, 1988), montane vole (Microtus montanus; Petterborg, 1978), meadow vole (Microtus pennsylvanicus; Dark and Zucker, 1984), tundra vole (Microtus oeconomus; Wang and Wang, 1996) and bank vole (Clethrionomys glareolus; Peacock et al, 2004).…”
Section: Introductionsupporting
confidence: 64%
“…The response of small mammals to cold stress differs, as is the case of Dicrostonyx groenlandicus and Mesocricetus auratus, the body weight of which increased during cold acclimation (Nagy, Negus, 1993;Janský, Haddad, Pospísilová, Dvorák, 1986). However, the body weight of Apodemus sylvaticus and Acomys cahirinus was not affected by cold acclimation (Klaus, Heldmaier, Ricquier, 1988;Khokhlova, Krasnov, Shenbrot, Degen, 2000;Gunduz, 2002); on the contrary, the body weight of Phodopussungorus, Microtusochrogaster, M. pennslvanicus and Clethrionomysglareolus decreased during cold acclimation (Klaus et al, 1988;Wiesinger, Heldmaier, Buchberger, 1989;Voltura, Wunder, 1998;Wang, Wang, 1990). In the study by Arnold, Richard (1987), cold exposure had no additional effect on body composition in physically active rats.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the NST capacity of Phodopus sungorus in winter increased by 70% compared to that in summer (Heldmaier et al 1982). The plateau pika (Ochotona curzoniae) and root vole (Microtus oeconomus) which live on the Qinghai-Tibet Plateau (Wang and Wang 1996) and Brandt's voles (M. brandti) that live in grasses of Inner Mongolia (Li and Wang 2005b) also showed similar patterns of adaptation. The increased energy expenditure in the cold can be compensated for by increasing energy intake and mobilizing body fat.…”
Section: Rmr Nst and Energy Intakementioning
confidence: 91%